Preliminary checklist of Auchenorrhyncha (Insecta: Hemiptera) from Reserva Ecológica del Pedregal de San Ángel, Distrito Federal, Mexico - Mariño-Pérez, Ricardo; Pacheco-Rueda, Iliana; Dietrich, Christopher (Instituto de Ecología, A.C., 2012)
We provide data on the fauna of Auchenorrhyncha from the Reserva Ecológica del Pedregal de San Ángel, Distrito Federal, to know its diversity. Thirty three species belonging to 8 families, 14 subfamilies and 28 genera were found. This is the first illustrated checklist for this area that, due to its location, origin and vegetation, is unique, protected by the UNAM and in process of being incorporated to the National System of Protected Natural Areas.